Development and Evaluation of Anti-tubercular Multiparticulate Novel Drug Delivery System - Chawla, Ruchi (iit bhu varanasi, 2015)
abstract available in the attachement file.
This thesis submitted by IIT BHU Varanasi, Phd scholar and supervised by Dr. B. Mishra
Keywords: Anti-tubercular Multiparticulat; Drug Delivery System